PS1 FAD mutant M146V decreases VEGF‐induced angiogenesis in brain endothelial cells. (December 2021) - Pandey, Rukmani; Robakis, Nikolaos K; Georgakopoulos, Anastasios
Abstract: Background: Alzheimer's disease (AD) is a multifactorial and progressive neurodegenerative disease, and the most common form of dementia. Cerebrovascular abnormalities and reduced vascular density are observed in human AD brains. Vascular pathology is an early event that contributes to the progression of AD and it can be caused by impaired angiogenesis. Brain angiogenesis in response to toxic insults is a reparative function regulated by endothelial cells (ECs); impairment in this function would render the brain vulnerable to insults. One of the most potent angiogenic factors, Vascular Endothelial Growth factor (VEGF), promotes angiogenesis by binding VEGFR2 receptor, a type I transmembrane protein (TMP). Most type I TMP are proteolytically processed by γ‐secretase, which has presenilin 1 (PS1) as a catalytic subunit. Mutations in PS1 cause Familial AD (FAD) and reduce the activity of γ‐secretase. We hypothesize that PS1 FAD mutants decrease the VEGF‐induced processing of VEGFR2 and brain angiogenesis. Targeting brain angiogenesis could have therapeutic value in AD. Method: Primary cortical endothelial cells (pCECs) were isolated and cultured from brains of wild type (WT) and PS1 M146V knockin mice, a "humanized" FAD model having the same genotype as in human FAD patients. We performed the in vitro angiogenesis assays sprouting on beads, migration and tube formation using pCEC cultures. Processing of VEGFR2 was studied in VEGFR2‐overexpressed HEK293 cells in presence or absence of VEGF‐A and γ‐secretase inhibitor (RO4929097) with western blotting. Result: We found that VEGFR2 is processed by γ‐secretase and that VEGF‐induced sprouting, tube formation, migration and angiogenic complexes between VE‐cadherin and Rok‐α kinase in pCEC are decreased in the presence of γ‐secretase inhibitor. We also found that pCEC expressing PS1 FAD mutant M146V do not sprout in response to VEGF as efficiently as WT cells. Conclusion: Our findings suggest that VEGFR2 is processed by γ‐secretase and that γ‐secretase promotes VEGF‐induced angiogenic functions of brain ECs. Our data also show that PS1 FAD mutant decreases angiogenic functions of pCEC. Importantly the effects of PS1 FAD mutants occur in the absence of amyloid plaques and neurofibrillary tangles indicating that PS1 FAD mutants can affect angiogenesis independent of the neuropathological hallmarks of AD.